Kelayakan Finansial Usaha Peternakan Ayam Broiler di Kecamatan Natar Kabupaten Lampung Selatan Studi Kasus Pola Kemitraan dan Pola Mandiri - Pratama, Nadia Lediana; Apriyani, Marlinda; Sutarni, Sutarni; Pratiwi, Dita (Universitas Galuh, 2026)
Broiler chicken farming plays an important role in providing high-quality and affordable animal protein, but this business faces challenges in the form of market competition, rising input prices, and falling selling prices, which can lead to losses. This study aims to calculate the costs, revenues, and profits of the business, analyze its financial feasibility, and assess the sensitivity of the broiler chicken business in Mandah Village with respondents who are independent and in partnerships. The results show that the independent model requires costs of IDR 778,185,000/year with revenues of IDR 618,440,000/year and profits of IDR 27,015,500/year, with an NPV of IDR 124,236,361 (>0), IRR of 14.5% (>6%), Net B/C of 1.43 (>1), and Payback Period of 1 year 7 months 27 days, making it feasible to operate. In the partnership model, the costs incurred are Rp3,911,100,000/year with revenues of Rp4,392,720,000/year and profits of Rp211,652,200/year, with an NPV analysis result of IDR 1,366,774,532 (>0), IRR of 37% (>6%), Net B/C of 2.78 (>1), and Payback Period of 5 months and 28 days, indicating that the business is very feasible to develop. Sensitivity analysis shows that both business models become unfeasible if there is a 17% increase in feed prices and a 5% decrease in selling prices. However, based on switching value, the independent model is still viable with a 5% increase in feed prices and a 2% decrease in selling prices, while the partnership model remains viable up to a 7% increase in feed prices and a 4% decrease in selling prices. Thus, both broiler chicken business models are viable, despite having different levels of risk to changes in input and output prices.